Odpowiedzi

Najlepsza Odpowiedź!
2010-01-30T21:10:16+01:00
Np.: 5 i 4/7 czytamy jako 5 całych i ułamek cztery siódme

2x+5y+3z=-1
0,5x-y=2-0,7z
11(x-y)=12+z

2x+5y+3z=-1
0,5x-y+0,7z=2 => y = 0,5x+0,7z-2
11x-11y-z=12

2x+5(0,5x+0,7z-2)+3z=-1
11x-11(0,5x+0,7z-2)-z=12

2x+2,5x+3,5z-10+3z=-1
11x-5,5x-7,7z+22-z=12

4,5x+6,5z=9 => 4,5x=9-6,5z => x=2-13/9 z
5,5x-8,7z=-10

5,5(2-13/9 z)-8,7z=-10
11 - 143/18z-8,7z=-10
(-143/18 - 87/10)z = -21 |*180
(-1430-1566)z=-3780
2996z=3780
z=1 i 784/2996
z=1 i 28/107

x = 2-13/9 * (1 i 28/107) = 2 - 1 i 88/107 = 19/107
x = 19/107

y = 0,5 * 19/107 +0,7 * 1 i 28/107 -2
y = 19/214 + 189/214 - 2 = -1 i 3/107

x = 19/107
y = -1 i 3/107
z = 1 i 28/107

Sprawdzenie:
2x+5y+3z=-1
38/107 - 5 i 15/107 + 3 i 84/107 = -1

0,5x-y=2-0,7z
19/214 + 1 i 3/107 = 2 - 189/214
1 i 25/214 = 1 i 25/214

11(x-y)=12+z
11(1 i 22/107) = 12 + 1 i 28/107
13 i 28/107 = 13 i 28/107
1 5 1